ANALISIS DAMPAK MASA PANDEMI TERHADAP PENDAPATAN PEDAGANG KAKI LIMA DI TAMAN TUGU KERIS KECAMATAN KOTA BARU KOTA JAMBI - Wahyudin Wahyudin; M. NAZORI MAJID; G.W.I. AWAL HABIBAH (CV. Aksara Global Akademia, 2024)
The COVID-19 pandemic and the imposition of Community Activity Restrictions (PPKM) in Jambi City had a direct impact on street vendors (PKL) at Tugu Keris Park, Jambi City. Therefore, traders must think of the right strategy in order to survive during the COVID-19 pandemic. The trader's strategy is a form of effort made during the face of the pandemic problem This study aims to analyze the impact of the pandemic on the income of street vendors in Taman Tugu Keris, Kota Baru District, Jambi City and to analyze the adaptation strategies applied by street vendors. five in Tugu Keris Park, Kota Baru District, Jambi City in dealing with COVID 19. This research approach uses a qualitative approach based on the philosophy of postpositivism. Data were collected using interviews and field observations. The results showed that there were three impacts of the COVID-19 pandemic by traders; first, the impact of declining income; second, the impact of disrupted economic activities of traders; third, the impact of financial expenditures that are not proportional to income. Meanwhile, the adaptation strategies found in the research on traders include; first is the corporate strategy by not increasing the selling price; both business unit strategies by providing bonuses; the three functional strategies with the use of social media for promotion. This research is expected to become knowledge and input for traders, government, and consumers when facing similar problems in the future.